Payroll Accounting System Evaluation: Evaluasi Sistem Akuntansi Penggajian - Rosalina Dwi Rahmayanti Diana Putri; Heri Widodo (Academia Open, 2021)
This study aims to determine the accounting system for the study that is applied in the process of running PR. Putra Maju Jaya, located in Tanggulangin, Sidoarjo. In this study, using a qualitative and descriptive approach to analyze and research the payroll accounting system in PR. Son Forward Jaya. Payroll accounting system is an accounting system that regulates the payroll process in a company or agency. The payroll accounting system that is running already meets the existing standards in the running process and is easier and simpler because it uses a computer-based system.